Academic Senate Minutes 2002-09-05 - Academic Senate:::::::::
Report from Chair. Agenda amended and approved. Minutes with amendments for May 5, 2002 and May 23, 2002 approved. Report from Provost. List of faculty eligible for Emeritus Status approved. Motion to request administration to present to Senate on parking issues approved. Reports from President of Associated Students, Chair-Elect, Statewide Senators, APC, EPC and SAC. Announcements from the floor.